Planck-scale effects on WIMP dark matter - Boucenna, Sofiane M.; Valle, Jose W.; Lineros, Roberto (Frontiers in Physics, 2014)
There exists a widely known conjecture that gravitational effects violate global symmetries. We study the effect of global-symmetry violating higher-dimension operators induced by Planck-scale physics on the properties of WIMP dark matter. Using an effective description, we show that the lifetime of the WIMP dark matter candidate can satisfy cosmological bounds under reasonable assumptions regarding the strength of the dimension-five operators. On the other hand, the indirect WIMP dark matter detection signal is significantly enhanced due to new decay channels.